REPRODUCTIVE BIOLOGY OF CATFISH (Mystus castaneus) IN THE TELABANG RIVER, SUBAH VILLAGE, TAYAN HILIR DISTRICTS, SANGGAU REGENCY, WEST KALIMANTAN PROVINCE. - Sukal Minarni (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT Catfish (M. castaneus) is one of fresh waterfish that has considerable potential for of consumption and processed fish.Management of catfish resources needs to be done, given its existence which is increasingly difficult to obtain in nature. This study aims to examine the biology of fish reproduction that includes sex ratio, gonad maturity level and fecundity. The method used in this research was purposive sampling. The Sampling was divided into three stations, that at station I wich  on the Upper Telabang River, station II was adjacent to oil palm plantations, station III was at down stream at the intersection with Lake Terentang. The  Sampling was done 3 times on basis biweekly from Desember 2018 to June 2019. Based on the results of the study, 277 fishes was obtained, consisting of 122 males and 155 females. The sex ratio of male and female baung fish is 1:127, wich it was balanced in the Telabang River Waters. The size of the length of the sex ratio in this study ranged from 62-141 mm. The maturity study was found in the rainy season generally in TKG I and TKG II in December 2018-April 2019 and in the summer (transition) dominated by TKG III and IV in May-June 2019. Total fecundity  as a whole ranges from 5,600-43,223 eggs with a length range between 85-141 mm and weighs 7-28 g. Baung fecundity has a close relationship between total length and total weight.Keywords: Fecundity, Gonad Maturity Level, Sex Ratio.